Characterization of a novel acetamidobenzoxazolone‐based PET ligand for translocator protein (18 kDa) imaging of neuroinflammation in the brain. (24th February 2014) - Tiwari, Anjani K.; Yui, Joji; Fujinaga, Masayuki; Kumata, Katsushi; Shimoda, Yoko; Yamasaki, Tomoteru; Xie, Lin; Hatori, Akiko; Maeda, Jun; Nengaki, Nobuki; Zhang, Ming‐Rong
Abstract We developed the novel positron emission tomography (PET) ligand 2‐[5‐(4‐[11C]methoxyphenyl)‐2‐oxo‐1, 3‐benzoxazol‐3(2H)‐yl]‐N‐methyl‐N‐phenylacetamide ([11C]MBMP) for translocator protein (18 kDa, TSPO) imaging and evaluated its efficacy in ischemic rat brains. [11C]MBMP was synthesized by reacting desmethyl precursor (1) with [11C]CH3I in radiochemical purity of ≥ 98% and specific activity of 85 ± 30 GBq/μmol (n = 18) at the end of synthesis. Biodistribution study on mice showed high accumulation of radioactivity in the TSPO‐rich organs, e.g., the lungs, heart, kidneys, and adrenal glands. The metabolite analysis in mice brain homogenate showed 80.1 ± 2.7% intact [11C]MBMP at 60 min after injection. To determine the specific binding of [11C]MBMP with TSPO in the brain, in vitro autoradiography and PET studies were performed in an ischemic rat model. In vitro autoradiography indicated significantly increased binding on the ipsilateral side compared with that on the contralateral side of ischemic rat brains. This result was supported firmly by the contrast of radioactivity between the ipsilateral and contralateral sides in PET images. Displacement experiments with unlabelled MBMP or PK11195 minimized the difference in uptake between the two sides. In summary, [11C]MBMP is a potential PET imaging agent for TSPO and, consequently, for the up‐regulation of microglia during neuroinflammation. <boxed-text content-type="graphic" id="jnc12670-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text> We developed 2‐[5‐(4‐[11C]methoxyphenyl)‐2‐oxo‐1, 3‐benzoxazol‐3(2H)‐yl]‐N‐methyl‐N‐phenylacetamide ([11C]MBMP) as a novel positron emission tomography ligand for imaging of translocator protein (18 kDa, TSPO) in the brain. [11C]MBMP exhibited high in vitro and in vivo specific binding with TSPO in the ischemic rat brain.